In-situ multiscale shear failure of a bistable composite tape-spring. (10th November 2020) - Wang, Bing; Seffen, Keith A.; Guest, Simon D.; Lee, Tung-Lik; Huang, Shi; Luo, Shifeng; Mi, Jiawei
Abstract: A bistable composite tape-spring (CTS) is stable in both the extended and coiled configurations, with fibres oriented at ±45°. It is light weight and multifunctional, and has attracted growing interest in shape-adaptive and energy harvesting systems in defence-, civil- and, especially aerospace engineering. The factors governing its bistability have been well-understood, but there is limited research concerning the mechanics of structural failure: here, we investigate the shear failure mechanisms in particular. We perform in-situ neutron diffraction on composite specimens using the ENGIN-X neutron diffractometer at Rutherford Appleton Laboratory (STFC, UK), and shear failure is characterised at both macroscopic and microscopic scales. Elastic and viscoelastic strain evolutions at different strain levels reveal the fundamentals of micromechanical shear failure, and their temperature dependency. Multiscale shear failure mechanisms are then proposed, which will benefit the optimisation of structural design to maintain structural integrity of CTS in aerospace applications. Graphical abstract: Image 1